Check Up Diabetic Foot, Deteksi Dini Risiko Luka Kaki Diabetes Pada Pasien Diabetes Mellitus di Makassar: Uji Sensitifitas dan Spesifisitas - Kasma Yuliani; Sulaeha Sulaeha; Sarina Sukri; Saldy Yusuf (Hasanuddin University, 2017)
The first step to detect the further risk of foot ulcer in diabetic patients is checking the diabetic food by using the Doppler Ankle Brachial Index (ABI) and monofilament test. However, these tools are not available yet in Indonesia. Therefore, it is needed the alternative of Doppler ABI and monofilament test. This study aims to evaluate the sensitivity and specificity of Ipswich test and palpation of the Dorsal Pedal and Posterior Tibial pulses. The current study was observational by using cross-sectional design and quantitative approach. The data collection is conducted through direct observation and questionnaire. In addition, the data analyses done are a description of the data while data interpretation based on the result of sensitivity and specificity test. The result showed that from four Community Health Center (Puskesmas) namely, Puskesmas Mangasa, Puskesmas Antang, Puskesmas Sudiang, and Puskesmas Jumpandang Baru, the sensitivity of Ipswich Touch Test (IpTT) to Monofilament Test ranged from 72.7% to 100%. In addition, the specificity test of IpTT to Monofilament Test was 33.3% to 100%. Meanwhile, the result of palpation of the Dorsal Pedal and Posterior Tibial pulses compared to Doppler ABI results 100% in sensitivity but the specificity was not available. This study shows that checkup with diabetic foot alternatively can be used to detect the risk of foot ulcer which simple, practice, and without special competency in usage.Keywords: checkup diabetic foot, Ipswich touch test, palpation, diabetes mellitus, diabetic foot ulcer